2019
DOI: 10.1017/s1744133119000148
|View full text |Cite|
|
Sign up to set email alerts
|

Transforming health care: the policy and politics of service reconfiguration in the UK's four health systems

Abstract: Public involvement in service change has been identified as a key facilitator of health care transformation (Foley et al., 2017) but little is known about how health policy influences whether and how organisations involve the public in change processes. This qualitative study compares policy and practice for involving the public in major service changes across the UK's four health systems (England, Northern Ireland, Wales and Scotland). We analysed policy documents, and conducted interviews with officials, sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…A comparative analysis of the UK’s four health systems highlights how the creation of trusting relationships and collaborative work is hardest in fragmented and unstable systems, such as England's NHS . Furthermore, a recent experiment aimed at creating a ‘space’ for co‐productive learning between researchers, clinicians, patients, carers, and managers also illustrated how even at a ‘distance’ from NHS spaces, the institutionalized scripts that structure power asymmetries are enormously difficult to disrupt .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative analysis of the UK’s four health systems highlights how the creation of trusting relationships and collaborative work is hardest in fragmented and unstable systems, such as England's NHS . Furthermore, a recent experiment aimed at creating a ‘space’ for co‐productive learning between researchers, clinicians, patients, carers, and managers also illustrated how even at a ‘distance’ from NHS spaces, the institutionalized scripts that structure power asymmetries are enormously difficult to disrupt .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent experiment aimed at creating a ‘space’ for co‐productive learning between researchers, clinicians, patients, carers, and managers also illustrated how even at a ‘distance’ from NHS spaces, the institutionalized scripts that structure power asymmetries are enormously difficult to disrupt . Nevertheless, both studies emphasize the essentiality of public support and the legitimization of ‘non‐professional’ knowledge for NHS transformations and collaborations, respectively, that in the current contestatory context requires specific attention . It is therefore concerning that in the NHSE guidance for delivering the STPs, PPI is referenced in isolation from discussions on the need to apply ‘social movement principles’ in health and care, indicating that patients and publics are not perceived to be a part of this ‘collective agency’ .…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere in Together for Mental Health distinct Welsh health policy themes emphasising continuous, open, engagement between policymakers, local managers and communities (Stewart et al 2020) are reflected in the idea that new relationships between the public and the mental health system are needed. This new relationship is premised on appeals to an approach which places people using services at the centre of their care as equal and active partners with professionals, and which tackles stigma, promotes equality and awareness of mental health issues across whole populations.…”
Section: Mental Health Policy Services and Practice In Walesmentioning
confidence: 99%
“…1 ‘The public’ has been widely identified as a problem for making significant changes to health care. 4 In response, studies have suggested involvement practices which might allow change to proceed, including: involving a wide range of stakeholders, early and prolonged engagement, and emphasizing clinical rationales for change processes. 5,6 These recommendations are in line with a wider view of public involvement as a coherent intervention with shared meaning which can bridge the troubled waters of service reconfiguration.…”
Section: Introductionmentioning
confidence: 99%